Youth spaces and places design for the development of socio-spatial communal values / Alice Sabrina Ismail - Ismail, Alice Sabrina (Faculty of Art and Design, 2025)
Youth is best seen as a transitional phase from the dependency of childhood to the independence of adulthood, typically spanning ages 18 to 24. This development period is vital, as young people experience a more fluid state than fixed age groups, encountering various challenges arising from technological advancements and socio-cultural issues. However, in the context of the built environment, most of the current designs, namely in urban cities, lack concern towards the youth community's needs and aspirations and are less empowering in both representation and inclusivity of youth through the participatory design processes. This resulted in the provision of spaces that are not autonomous, enclosed, unsafe, and inaccessible, which did not fully manage to engage and improve the well-being of youth communities. Furthermore, fewer studies have been provided on designing youth spaces and places in Malaysia based on theoretical design principles and approaches. This is because many past studies focus only on youth social empowerment and political engagement, technology advancement and utilization amongst youth, youth employment and macroeconomics factors, intellectual wellness, and youth resiliency in current society. This study, therefore, is crucial as it aims to highlight how to design better youth spaces and places that concern socio-spatial aspects towards enhancing the needs of youth and aiming at holistic empowerment of them, making them more resilient. To achieve this, best practices for recognizing the needs and interests of youth will be gathered collectively through a qualitative approach, utilizing critique sessions and focus group discussions with young people from diverse backgrounds as the primary methods for data collection. This involves referencing established case studies from literature reviews on prominent youth centres to support the findings. The insights gained are then translated into design strategies that emphasize socio-spatial elements, aiming to meet the needs of youth by fostering a sense of attachment and community. This paper benefits designers and authorities as a reference for creating better youth spaces and places to accommodate youth needs from different walks of life and backgrounds.